Desain dan Kinerja Unit Perlakuan Uap Panas (VHT) Untuk Disinfestasi Lalat Buah pada Penanganan Pascapanen Mangga - Rokhani Hasbullah; Agus Sutejo; Astu Unadi; Suparlan . (Jurnal Keteknikan Pertanian, 2009)
Formerly, chemical fumigation was used for disinfestation treatment, but now had been replaced bychemical-free disinfestations treatment such as vapor heat treatment (VHT). The objectives of this researchwere (1) to design the VHT Unit and testing its performances, and (2) to study the effect of the VHT methodand waxing on the fruit quality during storage of mango. The designs of VHT unit consist of water tank, filter,heater, water pump, differential pressure fan, atomizer, control panel and treatment chamber. Performanceof the unit showed that the temperature of the VHT chamber increased from ambient temperature of 30OCto setting point of 47OC in 70 minutes. Relative humidity of the VHT chamber was very high (more than90%) indicating the VHT unit was successful in being used for fruitfly disinfestations of fruit product. Usingsetting point of 46.5OC, the mango fruit core temperature reached temperature of 45.5-46.3OC in 130minutes. Mango ‘Gedong gincu’ were treated at 46.5OC for 10, 20, 30 minutes and control and then followedby waxing. The results showed that VHT of 10-30 minutes were not significantly affect the fruit quality.There were no significant changes in the fruit weight losses, hardness, color, soluble solid content, watercontent and vitamin C. VHT at 46.5OC for 20-30 minutes was effective to kill the fruitfly infested inside themangos and VHT followed by waxing was able to maintain mango quality during storage.Keywords : mango, fruit fly, heat quarantine treatment, vapor heat treatment (VHT)Diterima: 15 Januari 2008; Disetujui: 27 Agustus 2008